Management of early pregnancy bleeding in the accident and emergency department. Issue 3 (September 1988) - Gilling-Smith, C; Zelin, J; Touquet, R; Steer, P
Abstract : Over a period of 6 months, from February to July 1987, 26, 837 patients attended St Mary's A&E Department. Of these, 179 (0.7%) were complaining of bleeding in pregnancy of less than 20 weeks gestation. In May 1987 new management guidelines were introduced. These emphasised the importance of vaginal examination and the use of ultrasound to determine the viability of the pregnancy. As a result, the incidence of admission fell from 15 of 53 (28%) to 7 of 58 (12%), referral to the on-call gynaecologist from 23 of 53 (44%) to 13 of 58 (22%) and reattendance rates from 11 of 53 (15%) to 4 of 58 (4%) (all changes P less than 0.05).